2009
DOI: 10.1186/1471-2334-9-127
|View full text |Cite
|
Sign up to set email alerts
|

Black race as a predictor of poor health outcomes among a national cohort of HIV/AIDS patients admitted to US hospitals: a cohort study

Abstract: BackgroundIn general, the Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) population has begun to experience the benefits of highly active antiretroviral therapy (HAART); unfortunately, these benefits have not extended equally to Blacks in the United States, possibly due to differences in patient comorbidities and demographics. These differences include rates of hepatitis B and C infection, substance use, and socioeconomic status. To investigate the impact of these factors, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Hispanic culture treats elders with respect and views discharge to home as a more positive outcome [48]. Similarly to reports from other studies on blacks, we showed that they had a longer LOS and poorer discharge disposition, which might be related to their higher comorbidity burden [49,50]. On further analysis, our results showed that Blacks had the highest frequency of comorbidities (Deyo ≥1: 71.8%) vs. other races: Whites (68.34%), Hispanics (60.87%), and Asians and other races (65.4%).…”
Section: Discussionsupporting
confidence: 85%
“…Hispanic culture treats elders with respect and views discharge to home as a more positive outcome [48]. Similarly to reports from other studies on blacks, we showed that they had a longer LOS and poorer discharge disposition, which might be related to their higher comorbidity burden [49,50]. On further analysis, our results showed that Blacks had the highest frequency of comorbidities (Deyo ≥1: 71.8%) vs. other races: Whites (68.34%), Hispanics (60.87%), and Asians and other races (65.4%).…”
Section: Discussionsupporting
confidence: 85%
“…2 For example, from 1996 to 2006 African Americans with HIV/AIDS were 6 times more likely to be hospitalized for HIV/AIDS-related causes than wereWhites. 3,4 Further, in the period from 1987 to 2005, African American HIV mortality was 5 times higher than was that of Whites. 5,6 Moreover, these racial/ethnic disparities are increasing.…”
mentioning
confidence: 97%
“…[4][5][6][7][8][9][10][11] With the introduction of highly active antiretroviral therapy (HAART) in 1996, overall rates of hospitalization among HIV-infected patients declined significantly, particularly for AIDS-related issues, 9 though subsequently admissions for other causes (liver disease, non-opportunistic infections) increased 1,2,4 and demonstrated ongoing health disparities for women, 1 patients with serious mental illness, 10 injection drug users 7,10 and African Americans. 1,5,8,11 In the HAART era, national HIV hospitalization costs were 3.2 billion in 2005, 12 and costs for readmissions in this population may be up to 32% higher than the index admission. 13 Readmission rates within 30 days of discharge are 19-25% for HIV-infected patients, 14,15 which is comparable to Medicare beneficiaries, 16,17 congestive heart failure (CHF) patients, 18,19 and higher than published readmission rates for acute myocardial infarction (MI,18.9%) 20 and pneumonia (17.4%).…”
mentioning
confidence: 99%